Relasi Agama, Filsafat, dan Ilmu Menurut Pemikiran Al-Farabi: Relevansi Pengembangan Kurikulum Pendidikan Agama Islam di Era Kontemporer - Fina Hushunul Ahadiyah; Imron Rossidy (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study is motivated by the issue of fragmentation between religion, philosophy, and science, which has often been debated. In this regard, al-Farabi contributed his thoughts on the relationship between religion, philosophy, and science. The purpose of this study is to explain al-Farabi's thoughts on religion, philosophy, and science, and to explain their relevance to the development of the Islamic Education curriculum in the contemporary era. This study uses a qualitative method with a literature review. The results of this study conclude that al-Farabi's thoughts offer an approach that integrates religion, philosophy, and science. He places revelation and reason in harmony as sources of divine truth. The relevance of al-Farabi's thoughts to the Islamic Religious Education curriculum in the contemporary era lies in the importance of creating an educational system that balances spiritual, moral, and intellectual aspects. The Islamic Religious Education curriculum should aim to shape individuals who are religious, critical, and able to adapt to developments in science and technology. Keywords: Al-Farabi, Religion, Philosophy, Science, Islamic Religious Education Curriculum